An energy harvesting reactor for high voltage overhead insulated shield wires considering randomness of meteorological conditions. (15th August 2022) - Shu, Shengwen; Gai, Xiaolei; Qiu, Han; Tao, Yiqing; Huang, Yige
Abstract: Harvesting energy from the insulated shield wire with tuning is expected to be a possible solution to the problem of high power supply for online monitoring devices on high voltage overhead transmission lines. However, the randomness of meteorological conditions, such as wind and temperature, may cause fluctuations in the energy harvesting system's power and voltage. This paper presents an integrated energy harvesting reactor with both tuning and transformer functions, which can also consider the randomness of meteorological conditions. The statistical confidence interval of equivalent circuit parameters is numerically calculated based on meteorological data collected along a transmission line for a whole year from 2016 to 2020. On this basis, a combined magnetic circuit for the energy harvesting reactor is proposed to achieve a self-adaptive negative-feedback regulation, and parameter optimization is carried out and validated by field-circuit coupled simulation. Finally, an energy harvesting reactor prototype is developed and tested. The statistical analysis results on the equivalent circuit parameters show that they are approximately subject to Gaussian distribution. Besides, it is found from the experimental results that the maximum power under rated equivalent circuit parameters is 935 W, and the maximum power can reach 800–1000 W within the fluctuation range of equivalent circuit parameters considering meteorological randomness. Overall, the experimental results of the harvested power varying with load resistance conforms to the simulation results. Furthermore, compared to using a deeply saturated tuned reactor, the energy harvesting reactor shows better robustness to the randomness of meteorological conditions and the total harmonic content of output voltage is reduced by 64%. Therefore, the proposed energy harvesting reactor for high voltage overhead insulated shield sires shows more potential for a practical application than the existing methods. Highlights: An energy harvesting reactor for high voltage insulated shield sires is developed. The statistical confidence interval of equivalent circuit parameters is calculated. A combined magnetic circuit for the energy harvesting reactor is proposed. A field-circuit coupled simulation for the energy harvesting reactor is performed. An energy harvesting reactor prototype is developed and experimentally validated.